2008
DOI: 10.1509/jmkr.45.6.654
|View full text |Cite
|
Sign up to set email alerts
|

Interrupted Consumption: Disrupting Adaptation to Hedonic Experiences

Abstract: Six studies demonstrate that interrupting a consumption experience can make pleasant experiences more enjoyable and unpleasant experiences more irritating, even though consumers avoid breaks in pleasant experiences and choose breaks in unpleasant experiences. Across a variety of hedonic experiences (e.g., listening to noises or songs, sitting in a massage chair), the authors observe that breaks disrupt hedonic adaptation and, as a result, intensify the subsequent experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
158
1
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 171 publications
(174 citation statements)
references
References 21 publications
11
158
1
4
Order By: Relevance
“…Second, volitional disruption of daily activity has been shown to produce long-term changes in well-being (Lyubomirsky, Sheldon, and Schkade 2005). Finally, and most relevant to the current research, several enjoyable but monotonous experiences (i.e., sitting in a massage chair or listening to a looped song fragment) have been shown to be more enjoyable when disrupted than when experienced continuously (Nelson and Meyvis 2008). Together, these previous findings suggest that commercial interruptions may disrupt consumers' adaptation to television shows, thus restoring the intensity of the experience and increasing enjoyment of the program.…”
Section: Disrupting Adaptation To Television Programsmentioning
confidence: 69%
See 1 more Smart Citation
“…Second, volitional disruption of daily activity has been shown to produce long-term changes in well-being (Lyubomirsky, Sheldon, and Schkade 2005). Finally, and most relevant to the current research, several enjoyable but monotonous experiences (i.e., sitting in a massage chair or listening to a looped song fragment) have been shown to be more enjoyable when disrupted than when experienced continuously (Nelson and Meyvis 2008). Together, these previous findings suggest that commercial interruptions may disrupt consumers' adaptation to television shows, thus restoring the intensity of the experience and increasing enjoyment of the program.…”
Section: Disrupting Adaptation To Television Programsmentioning
confidence: 69%
“…Indeed, although people vary greatly in their intuitions about how hedonic experiences progress over time (Snell, Gibbs, and Varey 1995), they generally tend to underestimate the extent to which they adapt to experiences (Loewenstein and Frederick 1997). For instance, people underestimate their adaptation to a moderately irritating noise (Nelson and Meyvis 2008) and overestimate the duration of their affective reaction to discrete events (Wilson and Gilbert 2003). Given that people have difficulty predicting how their affective experiences evolve over time, they may underestimate the extent to which they adapt to an ongoing television show and thus fail to realize the beneficial, adaptationdisrupting effect of commercial interruptions.…”
Section: Disrupting Adaptation To Television Programsmentioning
confidence: 99%
“…Moreover, hedonic adaptation is rather robust and prevalent. People adapt to change in income (Di Tella, Haisken-De New, & MacCulloch, 2010), experiences (Epstein, Temple, Roemmich, & Bouton, 2009;Nelson & Meyvis, 2008;Nelson et al, 2009;Redden, 2008), academic careers (Gilbert, Pinel, Wilson, Blumberg, & Wheatley, 1998), and even to extreme life-changing events like incarceration (Zamble, 1992).…”
Section: Hedonic Adaptationmentioning
confidence: 99%
“…In one study, participants who experienced a short break while receiving a massage or listening to a pleasant song rated the experience as more pleasant than those who were uninterrupted during the massage or song (Nelson & Meyvis, 2008). The researchers argued that the participants' enjoyment of the activity was enhanced because the interruption helped to 'reset' their feelings of pleasantness and allowed them to savor the restarting of the experience.…”
Section: Long-distance Relationshipsmentioning
confidence: 99%
“…Although thus far we have only discussed adaptation to positive events and emotions, evidence suggests that variety of negative experiences can also impede adaptation. For example, researchers have found that people enjoy experiences with negative interruptions, such as irritating commercials or jarring noises, more than those same experiences without interruptions (Nelson & Meyvis, 2008;Nelson et al, 2009). If unhealthy relationships were negative all of the time, few people would remain in them.…”
Section: Abusive Relationshipsmentioning
confidence: 99%